Reproductive factors and menopausal hormone therapy and bladder cancer risk in the NIH‐AARP Diet and Health Study. Issue 2 (12th February 2013) - Daugherty, Sarah E.; Lacey, James V.; Pfeiffer, Ruth M.; Park, Yikyung; Hoover, Robert N.; Silverman, Debra T.
<x xml:space="preserve">Abstract</x> The incidence of bladder cancer among women is at least one‐third to one‐fourth that observed among men in many countries. Even after accounting for known risk factors, the reason for this gender disparity remains unexplained. We conducted a comprehensive evaluation of reproductive factors and exogenous hormone use with a primary focus on menopausal hormone therapy use and risk of bladder cancer in women in the NIH‐AARP Diet and Health Study. Reproductive and hormonal factors were ascertained on the baseline questionnaire in 1995–1996 among 201, 492 females who were followed until December 31, 2006. During follow‐up, 651 cases of bladder cancer were diagnosed. A subset of women provided detailed information on use of MHT in a second questionnaire in 1996–1997. In this analysis, 127, 361 females were followed through June 30, 2002 and 198 incident bladder cancer cases were identified. Cox proportional hazard models, adjusted for smoking status, cigarettes per day and body mass index using age as the time metric, were used to obtain hazard ratios (HRs). A reduced risk was observed among parous women (HR=0.76; 95% CI 0.62–0.93) and women who reported late age at menarche (≥15 years) (HR=0.57; 95% CI 0.39–0.84). Women who reported ever using estrogen and progestin therapy had a decreased risk (HR=0.53; 95% CI: 0.34–0.83) compared with women who did not report MHT use. No association was observed for estrogen only users (HR=0.82; 95% CI: 0.58–1.15). Our results suggest a putative role for sex hormones in the etiology of bladder cancer among women.